Alveolar Adenoma With CD34 Diffusely Positive Stromal Cells: A Rare Case Report and Literature Review - Gang Zhou MD, PhD; Ydamis Estrella Perez MD; Bing Leng MD, PhD (SAGE Publishing, 2023)
Alveolar adenoma (AA) is a rare type of pulmonary neoplasm showing proliferation of alveolar epithelium and septal mesenchyme. Clinically, AA is asymptomatic, benign, and usually diagnosed incidentally. Surgical excision is curative. The etiology of AA is controversial and the pathogenesis is unknown, but it is thought to stem from type II pneumocytes and fibroblasts or fibroblast-like cells. The stromal cells in AA may show rare staining for CD34. Diffuse CD34 positivity of the interstitial stromal cells has rarely been described and reviewed. Here, we report a case of AA with strong and diffuse CD34 staining in the stromal cells.